Cochrane and its prospects in Bosnia and Herzegovina: Relying on Cochrane Croatia - Mersiha Mahmić-Kaknjo; Livia Puljak; Filipa Markotić; Mahir Fidahić; Lejla Muhamedagić; Irena Zakarija-Grković (Acta Medica Academica, 2015)
In this article we describe Cochrane and its products: Cochrane systematic reviews (CSRs) and other Cochrane evidence. Cochrane is a unique, international, non-profit organisation that offers health care providers, health care consumers and other decision makers unbiased and highly reliable information on health, which is pivotal for conscientious and responsible decision making in overall healthcare. Cochrane offers the highest ranked evidence in Evidence Based Medicine (EBM) – systematic reviews. Currently, CSRs are freely available in BH, and therefore, they ought to be widely used, and understood. We will present the new Cochrane Strategy to 2020, which was the main topic of the 6th Croatian Cochrane Symposium (CroCoS), as well as explore prospects for spreading Cochrane activities to Bosnia and Herzegovina (BH), through collaboration with Cochrane Croatia. BH has no officially organized Cochrane activity, as yet. We hope that this article will raise awareness about Cochrane in BH, help promote its activities, and deepen the existing collaboration with Cochrane Croatia. There are already some changes being introduced concerning Cochrane – at least, in one half, the Federation of BH (FBH). Two documents symbolising official recognition of policy changes towards Cochrane have recently been published in the Official Gazette of FBH. Conclusion. Since founding a BH Cochrane Branch would be costly and difficult to achieve in a complicated environment, such as the one we have, BH could use the good will, experience, knowledge, and translated educational, training and web materials of Cochrane Croatia, particularly given the language similarities, to promote evidence based medicine in BH.